A method for determining the mass-molecular composition of microbial exopolysaccharides - Votselko, S.; Pirog, Tatiana; Malashenko, Yuri; Grinberg, Tamara (My University, 1993)
A method of determining the molecular mass composition of microbial exopolysaccharides (EPS) by centrifuging them in a combined density gradient created by NaCl and CsCl solutions and using the molecular mass of dextranes as standards is developed. The process of determining the molecular mass distribution pattern of EPS is simplified and made considerably less time-consuming. This method allows the analysis of native EPS with molecular masses ranging from 13 700 to 2 000 000.
Keywords: microbial exopolysaccharides; combined gradient; centrifuging; molecular mass composition; мікробні екзополісахариди; комбінований градієнт; центрифугування; молекулярно-масовий склад; кафедра біотехнології і мікробіології